Comparative efficacy of visuomotor behaviour rehearsal, biofeedback and combined interventions in performance of young athletes in East Coast of Malaysia - Huda, Foujia (2022)
The present study was carried out to investigate the significance of visuomotor behaviour rehearsal (VMBR), if any, on the ideomotor response related to erroneous performance outcomes identified in the participants. Identification of intricate relationships between certain physiological; psychophysiological; psychomotor and physical performance factors was done among young-adult high-performing athletes of Malaysia. Fifty-two athletes were recruited and provided with audio-visual feedback related to their erroneous performance outcomes, followed by an assessment of physiological parameters (viz. cardiovascular, autonomic measures of arousal) and corresponding psychological and psychomotor attributes (viz. cognitive flexibility, anxiety, reaction ability; motor and movement coordination; mood states and emotional stability) about performance excellence. Electrodermal evaluation of orienting reflex and electromyography analyses of evoked potential was carried out. Thereafter all of the participants were introduced to the evaluation of their movement errors. After that, they were randomly categorized into four groups, viz. one no-intervention control group; Experimental (Ex.) group I – who received training of VMBR only; Ex. Group II received training composite biofeedback training and the participants of Ex. Group III received training of VMBR along with biofeedback, following an identical training protocol (i.e., 25 min.s/day, 2 days/ week for 20 weeks). Midterm analyses of all of the baseline variables were done at the end of the tenth week, followed by post-intervention assessment, which was carried out at the end of the twentieth week. The sustainable impact of intervention techniques was evaluated by post-follow-up assessments. The Repeated measure of ANOVA was done to reveal the integral psychobiological processes underlying unconscious fear of apprehension leading toward dismal athletic performance. The outcome of this research will identify the ideal intervention techniques to be applied in improving the cognitively mediated perceptual-motor skills (for instance, serial skills involved in take-off and landing actions) in the athletes. A two-way repeated measure of ANOVA revealed that VMBR training contributed to the improvement of self-esteem, pleasant effect and resultant high level of emotional flexibility associated with changes in impulsivity and irritability evident among the athletes. Sc biofeedback, on the other hand, enhanced psychobiological (autonomic) competence in the athletes. This improvement was clear among the athletes who had relatively lower self-esteem; somatization crises (e.g., irritability, headache, pain, weakness etc.); autonomic startle response; lower extent of pleasantness and relatively higher extent of suspicious feelings. Apart from that, the combined intervention of VMBR and Sc biofeedback training was found effective in faster agility, speed and peak power output among the athletes, which were not evident in their counterparts in the no-intervention or control group and other intervention groups as well.